2018
DOI: 10.1002/pon.4687
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of the efficacy of cognitive behavior therapy on quality of life and psychological health of breast cancer survivors and patients

Abstract: Cognitive behavior therapy is an effective therapy for psychological symptoms of cancer survivors and patients, with meaningfully clinical effect sizes. These findings suggested that CBT should be used as the intervention for breast cancer survivors and patients when possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 51 publications
6
62
1
6
Order By: Relevance
“…A qualitative study of ET use found several patients reported difficulty remembering their medication, and those who were adherent described the use of a routine time for taking medication and reminders (such as alarms or pill‐boxes) as a facilitator . Importantly, studies examining racial difference in ET utilization have described racial differences in perceptions of tradeoffs as well as resource barriers, but have generally not described significant differences by age and race in habit formation , which we observe is nearly as large as the other, more commonly described, barriers.…”
Section: Discussioncontrasting
confidence: 53%
“…A qualitative study of ET use found several patients reported difficulty remembering their medication, and those who were adherent described the use of a routine time for taking medication and reminders (such as alarms or pill‐boxes) as a facilitator . Importantly, studies examining racial difference in ET utilization have described racial differences in perceptions of tradeoffs as well as resource barriers, but have generally not described significant differences by age and race in habit formation , which we observe is nearly as large as the other, more commonly described, barriers.…”
Section: Discussioncontrasting
confidence: 53%
“…The efficacy of Internet delivery of cognitive-behavioral techniques (CBT) is supported [19], as is CBT to reduce depression and stress in women with breast cancer [20]. Unguided Internet CBT psychosocial interventions also show promise [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…National Comprehensive Cancer Network Distress Management Guidelines support the use of psychosocial interventions that include cognitive behavioral techniques (CBT) and psychoeducation to reduce mild to moderate cancer‐related distress early in the course of care. A recent meta‐analysis of multimodal CBT, using a range of techniques, recommended CBT for women with breast cancer to reduce depression, anxiety, and stress . Greater uptake of such interventions by patients with cancer has been demonstrated when delivered early after diagnosis and remotely (eg, phone) rather than in person .…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis of multimodal CBT, using a range of techniques, recommended CBT for women with breast cancer to reduce depression, anxiety, and stress. 13 Greater uptake of such interventions by patients with cancer has been demonstrated when delivered early after diagnosis and remotely (eg, phone) rather than in person. 14 As technology moves forward, web-based delivery of interventions for stress reduction, including "low-intensity" CBT, 15 are increasing 16 and have shown efficacy whether clinically guided or self-managed by their intended users.…”
Section: Introductionmentioning
confidence: 99%